1997
DOI: 10.1111/j.1530-0277.1997.tb04471.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Exposure and Temporal Vulnerability: Regional Differences in Alcohol‐Induced Microencephaly as a Function of the Timing of Binge‐Like Alcohol Exposure During Rat Brain Development

Abstract: In humans, microcephaly (small head for body size) is a common feature of fetal alcohol syndrome. An analogous measure, termed microencephaly (small brain for body size), can be used for evaluating the detrimental effects of the differential timing of alcohol exposure on brain development in animal model systems. Timed-pregnant rats were exposed to binge-like alcohol during either the first 10 days (first trimester equivalent) or second 10 days of gestation (second trimester equivalent), or the combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 41 publications
1
72
0
Order By: Relevance
“…During the study period, men accounted for 81% of all binge-drinking episodes (Table 1), and they were approximately 3 times as likely as women to report binge drinking (eg, 22 …”
Section: Resultsmentioning
confidence: 99%
“…During the study period, men accounted for 81% of all binge-drinking episodes (Table 1), and they were approximately 3 times as likely as women to report binge drinking (eg, 22 …”
Section: Resultsmentioning
confidence: 99%
“…This concentration, while slightly greater then those associated with impaired mental capabilities and coordination (10 mM) or ataxia (20 mM) in humans is within the physiological relevant range. That is, this ethanol concentration, is similar to, or less, then the blood alcohol levels achieved in animal models of binge-like alcohol exposure [Thomas et al, 1996;Maier et al, 1997;Goodlett et al, 1997]. Further, studies in drinking women have reported blood alcohol concentrations above 50 mM [Urso et al, 1981;Church and Gerkin, 1988;Hammond et al, 1973;Wells and Barhill, 1996], including a report of one women with a blood alcohol level of approximately 330 mM (1.5%) [Johnson et al, 1982].…”
Section: Discussionmentioning
confidence: 78%
“…CONSEQUENCES OF PRENATAL TOBACCO AND NICOTINE EXPOSURE 7 (Probyn et al, 2012). Furthermore, the head and brain are not spared from the effects of prenatal ethanol exposure, with reduced head size reported in both humans (Day et al, 1989;Elliott et al, 2008;Feldman et al, 2012) and animal models (Maier et al, 1997;Kaminen-Ahola et al, 2010b).…”
Section: Evidence In Animal Modelsmentioning
confidence: 99%